2013
DOI: 10.1111/mec.12390
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression under chronic heat stress in populations of the mustard hill coral (Porites astreoides) from different thermal environments

Abstract: Recent evidence suggests that corals can acclimatize or adapt to local stress factors through differential regulation of their gene expression. Profiling gene expression in corals from diverse environments can elucidate the physiological processes that may be responsible for maximizing coral fitness in their natural habitat and lead to a better understanding of the coral's capacity to survive the effects of global climate change. In an accompanying paper, we show that Porites astreoides from thermally differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
231
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(271 citation statements)
references
References 99 publications
(115 reference statements)
22
231
4
Order By: Relevance
“…Inshore and offshore adult P. astreoides display gene expression patterns that may reflect alternative energy allocation strategies (Kenkel et al, 2013b). Similar variation in recruit populations could underpin the differences in growth rates through time and in response to temperature stress, but additional transcriptomic studies are needed to validate this hypothesis.…”
Section: Population-level Variation In Temperature Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Inshore and offshore adult P. astreoides display gene expression patterns that may reflect alternative energy allocation strategies (Kenkel et al, 2013b). Similar variation in recruit populations could underpin the differences in growth rates through time and in response to temperature stress, but additional transcriptomic studies are needed to validate this hypothesis.…”
Section: Population-level Variation In Temperature Tolerancementioning
confidence: 99%
“…These populations harbor indistinguishable Symbiodinium phylotypes but hosts are significantly genetically differentiated (Kenkel et al, 2013a) and exhibit divergent gene expression patterns (Kenkel et al, 2013b) suggesting that the coral host has a more prominent role in thermal adaptation in this species. However, it is not clear if observed thermotolerance differences in these populations are the result of heritable genetic variation or long-term acclimatization to their native habitat.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the upregulation of collagen-associated proteins has been found in more thermally-tolerant individuals , Kenkel et al 2013. However, in the present study collagen was upregulated for both species in Summer 2013, suggesting that collagen does not play a role in the different susceptibilities of D. labyrinthiformis and P. strigosa.…”
Section: Discussioncontrasting
confidence: 69%
“…Heat shock proteins (HSPs) are commonly the focus of cnidarian thermal stress studies (Leggat et al 2011), however they may not tell the entire story, as they are absent in several studies of coral heat stress (the present study and , and have been shown to decrease in expression levels a mere 10 hours after the initial temperature change (Rodriguez-Lanetty et al 2009). Heat shock proteins can also be unexpectedly downregulated, for example HSP90 was downregulated in Porites astreoides (Kenkel et al 2013). Sharp et al (1997) reported a downregulated in HSP70 in Goniopora dljiboutiensis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation